Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kecerdasan Spiritual Siswa SMP Negeri 02 Kartasura - Syahri Abdidurrohman; Hafidz Hafidz (Kamaya: Jurnal Ilmu Agama, 2026)
This study aims to describe the role of Islamic Religious Education teachers and the strategies implemented in improving students' spiritual intelligence at SMP Negeri 02 Kartasura. This study uses a descriptive qualitative approach and data collection techniques through interviews, observation, and documentation. The results of the study indicate that Islamic Religious Education teachers have a role as role models (uswatun hasanah), mentors, educators, and motivators to develop students' spiritual intelligence through a humanistic approach and teacher mentoring program. In addition, the strategies implemented include planning, habituation, practice, and evaluation of religious activities, namely praying together, tadarus (recitation of the Koran), congregational prayer, memorization of the Koran, and religious extracurricular activities. These strategies have been proven to be able to shape students' spiritual habits through the integration of religious activities into the school culture. These findings indicate that the success of improving students' spiritual intelligence is largely determined by the consistency of the teacher's role and the systematic implementation of religious habituation strategies in schools.